2022
DOI: 10.1111/ppl.13775
|View full text |Cite
|
Sign up to set email alerts
|

The MYB33, MYB65, and MYB101 transcription factors affect Arabidopsis and potato responses to drought by regulating the ABA signaling pathway

Abstract: Drought is one of the main climate threats limiting crop production. Potato is one of the four most important food crop species worldwide and is sensitive to water shortage. The CBP80 gene was shown to affect Arabidopsis and potato responses to drought by regulating the level of microRNA159 and, consequently, the levels of the MYB33 and MYB101 transcription factors (TFs). Here, we show that three MYB TFs, MYB33, MYB65, and MYB101, are involved in plant responses to water shortage.Their downregulation in Arabid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 67 publications
(108 reference statements)
0
3
0
Order By: Relevance
“…The expression of 25 TFs including ve AP2/ERF, ve NAC, eight RING-type zinc ngers were induced after 18 days of drought treatment (Table S5), suggesting their potential importance for drought tolerance in white spruce. The two MYB sequences identi ed in this study had homologies with putative Arabidopsis thaliana proteins known to enhance protection against oxidative damage or to be involved in growth, phenylpropanoid biosynthesis, and the ABA signaling pathway [127][128][129]. Drought-induced AP2/ERF genes in our study were close homologs to ethylene responsive elements in other species [130].…”
Section: Drought-responsive Genes Coding For Protective Defense and S...mentioning
confidence: 88%
“…The expression of 25 TFs including ve AP2/ERF, ve NAC, eight RING-type zinc ngers were induced after 18 days of drought treatment (Table S5), suggesting their potential importance for drought tolerance in white spruce. The two MYB sequences identi ed in this study had homologies with putative Arabidopsis thaliana proteins known to enhance protection against oxidative damage or to be involved in growth, phenylpropanoid biosynthesis, and the ABA signaling pathway [127][128][129]. Drought-induced AP2/ERF genes in our study were close homologs to ethylene responsive elements in other species [130].…”
Section: Drought-responsive Genes Coding For Protective Defense and S...mentioning
confidence: 88%
“…It is worth noting that, despite the negative impact of PeMYB33 on growth and development, it may play an important role in responding to both biotic and abiotic stress. Research shows that drought treatment enhances stomatal closure in OE‐MYB33 plants, thereby increasing their drought tolerance (Wyrzykowska et al., 2022). Furthermore, MYB33 can bind to the LEAFY promoter, promoting its expression, and thus influencing the flowering time (Achard et al., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, hypo-DMR-associated upregulated DEGs that might be regulated by TFs were identified, including MYB101 ( AT2G32460 ) and ATGH3.12 ( AT5G13320 ). Previous research indicates that MYB101 functions as a constructive regulatory element in ABA-stimulated growth cessation, and an ineffective MYB101 mutant reduces the sensitivity of plants to ABA [ 43 , 44 ]. It has been observed that ABA has the potential to induce senescence in leaves through a pathway that is independent of ethylene.…”
Section: Discussionmentioning
confidence: 99%